جماليات البديع الفني وأثره الدلالي في شعر ابن الوردي - العنبكي, ساهره عدنان وهيب (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
Badi is one of the arts that seeks to achieve creativity, through harmony, cohesion, coloring or decoration in the literary text, as well as the semantic capabilities granted by the original context of the sentence. Art affirms that the backbone of textual creativity is not devoid of rhythm. It is the essence of the arts and the poetics of literary texts, as well as its sensual pleasure that is harmonious with the human soul that yearns for toning, and the intellectual and aesthetic pleasure of those connoisseurs of works of art. or meaning. As for the application, it is in the poetry of Ibn al-Wardi, in which the methods are abundant, which calls for study, revealing and interpreting the dominant ones in a way that serves the rhetorical lesson and its aesthetic impact.